Association between sleep duration, sleep trouble and all-cause mortality in individuals with hyperuricemia in the United States - Dai, Yuanhui; Sun, Xiangyu; Zhang, Ge; Cui, Chunying; Wu, Xiaoli; Aizezi, Yierzhati; Kadier, Kaisaierjiang (Frontiers in Public Health, 2025)
ObjectivesDespite the crucial role of sleep quality in hyperuricemia onset and progression, there is limited evidence on sleep interventions to improve outcomes for hyperuricemic individuals. This study aims to investigate the effects of sleep duration and sleep difficulties on all-cause mortality in this population.Materials and methodsWe conducted a secondary analysis of the National Health and Nutrition Examination Survey (NHANES) data from 2007 to 2018, including 5,837 participants. We employed weighted multivariable Cox proportional hazard models to evaluate the independent predictive value of sleep duration and trouble for all-cause mortality. Restricted cubic splines and segmented Cox proportional hazard models were used to examine threshold effects.ResultsDuring a mean follow-up of 6.5 years, 906 participants experienced all-cause mortality. After adjusting for confounders, both short (< 7 h; HR = 1.25; 95%CI: 1.04, 1.51; p = 0.018) and long (>9 h; HR = 1.50; 95%CI: 1.10, 2.04; p = 0.011) sleep durations were associated with increased all-cause mortality. The threshold analysis identified an optimal sleep duration of 7.23 h, and when sleep duration was below 7.23 h, it was inversely related to mortality (HR: 0.879; 95% CI: 0.788, 0.981; p = 0.022). Conversely, when sleep duration exceeded 7.23 h, it was positively associated with mortality (HR: 1.187; 95% CI: 1.066, 1.320; p = 0.002).ConclusionSleep duration is U-shapedly associated with all-cause mortality among individuals with hyperuricemia in the United States. However sleep trouble was not associated with all-cause mortality. Maintaining optimal sleep duration helps improve the prognostic survival rates of those with hyperuricemia.